Developing e-Market Information System Android Based in Minahasa Regency - Ratumbuisang, Keith Francis; Ratumbuisang, Yosua Fitsgerald; Parinsi, Mario Tulenan (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
In the midst of the COVID-19 pandemic which limits humans from interacting directly, the trade sector, in this case buying and selling in traditional markets, is hampered. Therefore, the researcher took the initiative to create an innovation, namely an Android-based E-Market Information System application that helps improve the community's economy during the COVID-19 pandemic, while providing an alternative to digital sales when entering the new normal period. In this study also tested the feasibility level of the software that has been made. This research method is Design and Build using the system development method with the Waterfall model. Software testing is done through black-box testing, McCall's Quality Factor as an indicator to determine the level of software feasibility with a measurement scale using a Likert Scale. Interviews and questionnaires are techniques used to collect data, while data analysis techniques use descriptive quantitative analysis. The mandatory output targeted for this research is developing an E-Market information system in Minahasa. In addition, the results of this study are to be published in an International Journal, namely the Journal of Mobile Computing and Multimedia Communications as an additional output